Ambiguitas Makna dalam Bab IV Perkawinan Kitab Undang-Undang Hukum Perdata Indonesia - Khurnia Haty; Asih Ria Ningsih (Institut Agama Islam Sunan Giri Ponorogo, 2025)
This research examines linguistic ambiguity in Chapter IV on Marriage in the Indonesian Civil Code (KUHPerdata), highlighting how unclear legal language leads to multiple interpretations. The study aims to identify the forms and meanings of ambiguity present in the chapter. Using a qualitative descriptive method, data were collected through a listening technique and analyzed using the intralingual equivalence method. Findings reveal that ambiguity still occurs in various articles, resulting from grammatical and lexical issues. A total of 46 ambiguous articles were identified, consisting of 34 cases of grammatical ambiguity and 12 of lexical ambiguity. However, this research focuses on 20 representative data points—10 lexical and 10 grammatical. Lexical ambiguities stem from imprecise diction, while grammatical ambiguities arise from sentence structures that do not align with proper Indonesian grammar. These ambiguities indicate a need for language refinement in the legal text to avoid misinterpretation and ensure legal certainty.